2010
DOI: 10.1002/aur.148
|View full text |Cite
|
Sign up to set email alerts
|

Prototypical category learning in high‐functioning autism

Abstract: An ongoing debate in developmental cognitive neuroscience is whether individuals with autism are able to learn prototypical category representations from multiple exemplars. Prototype learning and memory were examined in a group of high-functioning autistic boys and young men, using a classic paradigm in which participants learned to classify novel dot patterns into one of two categories. Participants were trained on distorted versions of category prototypes until they reached a criterion level of performance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 40 publications
3
53
0
1
Order By: Relevance
“…Two previous studies (Church et al, 2010; Vladusich et al, 2010) have utilized a random dot pattern task to examine prototype formation in autism. As mentioned above, the fact that both tasks provided feedback to participants about whether each stimulus had been accurately categorized could have interfered with learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two previous studies (Church et al, 2010; Vladusich et al, 2010) have utilized a random dot pattern task to examine prototype formation in autism. As mentioned above, the fact that both tasks provided feedback to participants about whether each stimulus had been accurately categorized could have interfered with learning.…”
Section: Discussionmentioning
confidence: 99%
“…Church et al (2010) and Vladusich et al (2010) used the random dot pattern task or a variation of it, but participants were trained with corrective feedback after making a response. Maddox et al (2008) demonstrated that feedback can actually hurt learning of perceptual categories, such as in the random dot pattern task, by engaging the neural system supporting explicit, rule-based category learning.…”
Section: Introductionmentioning
confidence: 99%
“…However, even when apparently normal categorization is observed, individuals with high-functioning ASD (HFASD) showed impairments in learning or generalization (Bott et al, 2006;Gastgeb et al, 2012;Froehlich et al, 2012;Soulières et al, 2011;Vladusich et al, 2010), differences in brain activity (Schipul, 2012), or subgroups who showed abnormal generalization (Molesworth et al, 2008), suggesting that the neural mechanisms or processes involved may differ. This contrasts with relatively consistent findings of spared simple explicit rule formation and implicit associative/statistical learning in individuals with ASD (e.g., Brown, Aczel, Jimenez, Kaufman, & Grant, 2010, contextual cueing, serial reaction time, artificial grammar learning, and probabilistic classification; Klinger and Dawson, 2001, single-dimensional rules).…”
mentioning
confidence: 99%
“…Individuals with autism in general appear equally subject to the influence of prototypes as control participants (e.g. Gastgeb et al, 2006;Molesworth, Bowler, & Hampton, 2005;Vladusich, Lafe, Kim, Tager-Flusberg, & Grossberg, 2010). One study that modeled categorization performance with a quantitative exemplar model, the general context model (GCM, Nosofsky, 1986) reported no differences between an ASD group and control group.…”
mentioning
confidence: 99%